Comparative metabarcoding analysis of phytoplankton community composition and diversity in aquaculture water and the stomach contents of Tegillarca granosa during months of growth. (February 2023) - Huang, Hailong; Chen, Sentao; Xu, Zhihui; Wu, Yanhua; Mei, Limin; Pan, Yuanbo; Yan, Xiaojun; Zhou, Chengxu
Abstract: Filter-feeder bivalves and phytoplankton are interdependent. Their interaction plays important role in estuarine and coastal ecosystem. The correlation between bivalve feeding and phytoplankton is highly species specificity and environment dependent. In the background of miniature and nondiatom trend of phytoplankton in coastal seawaters, how bivalve respond and how the response play roles in the phytoplankton community are poorly known. In the present study, by applying DNA metabarcoding approach based on plastid 23S rDNA, this question was addressed by comparing the phytoplankton composition in the seston and the stomach content of blood clam Tegillarca granosa sampled during the growth period from March to November 2020 in an experimental farm on tidal flat in Xiangshan Bay, East China Sea. The result showed that, a total of seven phyla, 55 genera and 73 species of phytoplankton were identified for all samples. Chlorophyta, Bacillariophyta, and Cyanobacteria were found to be three dominant phyla both in the stomach contents and seston. High diversity of pico-sized phytoplankton, which was easy overlooked by microscopy, was revealed both in seston and stomach contents. This result indicated that the clam was able to feed on the pico-sized algae. At the genus level, the most abundant genera were the pico-sized green alga Ostreococcus (6.12 %–67.88 %) in seston and Picochlorum (4.07 %–35.33 %) in the stomach contents. In addition, microalgae of high nutritional value showed trend of higher proportion in stomach contents than that in seston, especially in July and September when significant growth of T. granosa was observed during this period (the body size increased 155 %). Biodiversity of phytoplankton in the seston was totally higher than that in stomach content, however, the changes among the months showed respective trend. Especially in July when the biodiversity was the lowest in seston, that in the stomach content showed the highest. The results indicated that blood clam farming might influence the phytoplankton composition, including those of pico-sized level, although the particular species in seston were mainly correlating with the dominant environmental factors such as temperature, salinity, pH respectively. These results extend the understanding of roles that bivalve aquaculture may play in the changing of coastal phytoplankton community. Highlights: The metabarcoding approach revealed highly diverse and small phytoplankton, which were easy to overlook by microscopy. Chlorophyta, Bacillariophyta and Cyanobacteria were the three dominant phyla. Microalgae with high nutritional quality showed higher probability of presentation in stomach content than in seston.